Ecological and morphological traits of the invasive pumpkinseed (Lepomis gibbosus) in Serbian lowland reservoirs - Subotić, Srđan; Cvijanović, Gorčin; Jaćimović, Milica; Đikanović, Vesna; Jovičić, Katarina; Nikolić, Dušan (Archives of Biological Sciences, 2026)
Paper description: Pumpkinseed (Lepomis gibbosus) is one of the most widespread invasive freshwater fish in Europe, established in Serbian reservoirs. The age structure, growth, body shape, condition, and diet of 434 individuals from five eutrophic lowland reservoirs were analyzed using scale reading, growth modelling, geometric morphometrics, and gut content analysis. Populations exhibited seven age classes, slow growth with positive allometry, good condition, significant body shape variation, and diets dominated by aquatic invertebrates, with high inter-reservoir similarity but variable niche breadth. These results demonstrate the strong ecological flexibility of pumpkinseed in artificial waterbodies and provide a scientific basis for improved monitoring and management. Abstract: This study investigates the ecological and morphological traits of invasive pumpkinseed (Lepomis gibbosus) in five lowland reservoirs in Serbia. A total of 434 specimens were collected in October 2020 and analyzed for population structure and growth parameters, body shape, condition, and diet. The population consisted of seven age classes, with three distinct age structures identified across the analyzed reservoirs. The highest growth increment occurred during the first year of life. Compared to other European populations, this cohort exhibited the slowest overall growth, characterized by the lowest k values. However, the specimens maintained a robust body condition (K>1) and displayed positive allometric growth (b>3). The autumn diet included 14 prey categories, with Chironomidae larvae being the most prominent. Mean dietary similarity between reservoirs was 75.7%, indicating significant dietary niche overlap. Niche breadth analysis showed greater dietary specialization in Topola and Kudreč 2, and lower specialization in Jatagan, where prey diversity was highest. These findings offer valuable insights into the adaptive potential and ecological impact of this invasive species and can support future management and monitoring strategies.